(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There are many applications which makes use of pattern matching algorithm. Most of current websites implements pattern matching algorithm in order to display the results faster. There exist different kind of data such as image, text, video, audio. In order to deal with such kind of data different pattern matching algorithms are used. One algorithm performs well in particular type of data, while it degrades in other kind of data. Our aim is to find best pattern matching algorithm.One of the key aspects of any string-matching algorithm is how fast the string matching is done along with the degree of search performance. This paper offers a survey on various String-matching algorithms along with the comparative analysis to provide a brief idea regarding the better algorithm for improving the search performance..